SINERGISME CENDAWAN ENTOMOPATOGEN Lecanicillium lecanii DENGAN INSEKTISIDA NABATI UNTUK MENINGKATKAN EFIKASI PENGENDALIAN TELUR KEPIK COKLAT Riptortus linearis PADA KEDELAI - Yusmani Prayogo (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
The aim of the research was to study the synergism of entomopathogenic fungi Lecanicillium lecanii with botanical insecticides to control brown stink bug. The research was carried out in the field experiment station (Kendalpayak) of Indonesian Legume and Tuber Crops Research Institute (ILETRI). Randomized block design (RBD) was used, each treatment was repeated three times. The treatments were three types of botanical insecticides i.e; Aglaia odorata leaf powder (ALP), Annona squamosa seed powder (ASP), and Jatropha curcas seed powder (JSP) of 25, 50 and 75 g/l respectively were combined with the conidia of L. lecanii. The results showed that the addition of botanical insecticides into the media can improve growth and development of the fungus L. lecanii. The higher dose of botanical insecticide in combination with the L. lecanii, the greater efficacy of both agents are in controlling brown stink bug eggs. Synergism of combination of L. lecanii and botanical insecticides were shown from the number of unhatched eggs (above 77%) compared with a single application. The fewer number of brown stink bug eggs hatching, caused the limited number of brown stink bug can developed become adult, resulting reduced soybean seeds and pods damaged. The combination of L. lecanii and botanical insecticides was able to maintain weight of soybean seed up to 35% compared to single treatment (control). The combination of L. lecanii and ASP and JSP botanical pesticides were more synergist compared with combination of L. lecanii with ALP. Dose of 50 g/l botanical pesticide JSP and ALP were combined with the L. lecanii was an optimal dose to control of brown stink bug eggs.